Non-invasive cardiac kinetic energy distribution: a new marker of heart failure with impaired ejection fraction (KINO-HF) - De Keyzer, Eva; Hossein, Amin; Rabineau, Jeremy; Morissens, Marielle; Almorad, Alexandre; van de Borne, Philippe (Frontiers in Cardiovascular Medicine, 2023)
Background Heart failure (HF) remains a major cause of mortality, morbidity, and poor quality of life. 44% of HF patients present impaired left ventricular ejection fraction (LVEF). Kinocardiography (KCG) technology combines ballistocardiography (BCG) and seismocardiography (SCG). It estimates myocardial contraction and blood flow through the cardiac chambers and major vessels through a wearable device. Kino-HF sought to evaluate the potential of KCG to distinguish HF patients with impaired LVEF from a control group. Methods Successive patients with HF and impaired LVEF (iLVEF group) were matched and compared to patients with normal LVEF ≥ 50% (control). A 60 s KCG acquisition followed cardiac ultrasound. The kinetic energy from KCG signals was computed in different phases of the cardiac cycle (iKsystolic;ΔiKdiastolic) as markers of cardiac mechanical function. Results Thirty HF patients (67 [59; 71] years, 87% male) were matched with 30 controls (64.5 [49; 73] years, 87% male). SCG ΔiKdiastolic, BCG iKsystolic, BCG ΔiKdiastolic were lower in HF than controls (p < 0.05), while SCG iKsystolic was similar. Furthermore, a lower SCG iKsystolic was associated with an increased mortality risk during follow-up. Conclusions KINO-HF demonstrates that KCG can distinguish HF patients with impaired systolic function from a control group. These favorable results warrant further research on the diagnostic and prognostic capabilities of KCG in HF with impaired LVEF. Clinical Trial Registration: NCT03157115.